TP53 in Myelodysplastic Syndromes - Yan Jiang (MDPI AG, 2021)
Myelodysplastic syndromes (MDSs) are heterogeneous for their morphology, clinical characteristics, survival of patients, and evolution to acute myeloid leukemia. Different prognostic scoring systems including the International Prognostic Scoring System (IPSS), the Revised IPSS, the WHO Typed Prognostic Scoring System, and the Lower-Risk Prognostic Scoring System have been introduced for categorizing the highly variable clinical outcomes. However, not considered by current MDS prognosis classification systems, gene variants have been identified for their contribution to the clinical heterogeneity of the disease and their impact on the prognosis. Notably, TP53 mutation is independently associated with a higher risk category, resistance to conventional therapies, rapid transformation to leukemia, and a poor outcome. Herein, we discuss the features of monoallelic and biallelic TP53 mutations within MDS, their corresponding carcinogenic mechanisms, their predictive value in current standard treatments including hypomethylating agents, allogeneic hematopoietic stem cell transplantation, and lenalidomide, together with the latest progress in TP53-targeted therapy strategies, especially MDS clinical trial data.